2006
DOI: 10.1002/mds.21290
|View full text |Cite
|
Sign up to set email alerts
|

Lower low‐density lipoprotein cholesterol levels are associated with Parkinson's disease

Abstract: The apolipoprotein E (APOE) ε2 allele has been associated with both Parkinson's disease (PD) and lower low density lipoprotein cholesterol (LDL-C). The study is to test the hypothesis that lower LDL-C may be associated with PD. This case-control study used fasting lipid profiles obtained from 124 PD cases and 110 controls, the PD cases recruited from consecutive cases presenting at our tertiary Movement Disorder Clinic, and controls recruited from the spouse populations of the same clinic. Multivariate odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
190
4
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(215 citation statements)
references
References 25 publications
20
190
4
1
Order By: Relevance
“…16 Interestingly, the only previous study to examine associations between statins and prevalent PD also reported a protective effect, even after adjustment for LDL-C concentration. 4 However this study heavily relied on statin use for the post-diagnosis period and prevalent PD cases with a moderately to long duration of disease. Post-diagnosis statin use may not properly reflect pre-diagnosis use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Interestingly, the only previous study to examine associations between statins and prevalent PD also reported a protective effect, even after adjustment for LDL-C concentration. 4 However this study heavily relied on statin use for the post-diagnosis period and prevalent PD cases with a moderately to long duration of disease. Post-diagnosis statin use may not properly reflect pre-diagnosis use.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Two studies reporting an association between low cholesterol and PD suggest that low cholesterol or low Co-enyzme Q10 increase the risk of Parkinson's disease (PD) thus raising the possibility that statin use might be harmful to the dopaminnergic system. 4,5 On the other hand there is considerable biological evidence suggesting that statins have neuroprotective properties. Statins scavenge oxygen-derived free radicals, which studies suggest may help ameliorate free radical injury.…”
Section: Introductionmentioning
confidence: 99%
“…However, for high serum triglycerides, the multivariate analyses showed lower PD risk (OR 0.49, 95% CI 0.27-0.89) [631]. A hospital-based case-control study, in which spouses of patients from a movement disorder clinic were used as controls, reported increased PD risk with lower serum low-density lipoprotein (LDL) cholesterol (OR for lowest category versus highest 2.6, 95% CI 1.1-6.0), but no significant association for total and high-density lipoprotein (HDL) cholesterol [638].…”
Section: Vascular Diseasesmentioning
confidence: 99%
“…A strong association between lower cholesterol and Parkinson disease risk has been reported, such that each mmol/L increase in total cholesterol was accompanied by a 23% decrease in the risk of developing Parkinson disease. The risk reduction was significant in women but not in men [24].…”
Section: Review Of the Statin Sagamentioning
confidence: 77%